Crystal structure and supramolecular features of a bis-urea-functionalized pillar[5]arene - Mickey Vinodh; Fatemeh H. Alipour; Talal F. Al-Azemi (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The crystal structure of a bis-urea derivative based on A1/A2-functionalized pillar[5]arene (DUP) that encapsulates dimethyl formamide (DMF) inside the macrocyclic cavity is reported. The crystal structure of DUP·DMF, C63H70N4O12·C3H7NO, reveals that out of two urea functionalized spacers, one arm is oriented above the macrocyclic cavity with strong hydrogen-bonding interactions between the urea H atoms and DMF guest, whereas, the other arm is positioned away from the macrocycle, leading to intermolecular hydrogen-bonding interactions between the urea H atoms of two adjacent pillar[5]arene macrocycles, resulting in the formation of a supramolecular dimer.